Prognostic Value of Motor Timing in Treatment Outcome in Patients With Alcohol- and/or Cocaine Use Disorder in a Rehabilitation Program - Young, Susanne Yvette; Kidd, Martin; van Hoof, Jacques J. M.; Seedat, Soraya (Frontiers in Psychology, 2018)
Introduction: Individuals with Substance Use Disorder (SUD) often have cognitive deficits in multiple domains, including motor timing deficits, with recovery times of up to 1 year. Cognitive deficits influence treatment outcomes and abstinence. To our knowledge, timing deficits have not been investigated with regard to treatment outcome and relapse. Methods: This prospective study tested the prognostic value of motor timing in SUD with regard to treatment outcome. The study sample consisted of 74 abstinent in-patients at a private treatment programme for drug/alcohol dependence at the Momentum Mental Healthcare clinic in Somerset West, South Africa, diagnosed with alcohol and/or cocaine dependence. Participants were tested at three points: (i) Within 72 hours of the start of the treatment programme (ii) after completion of the treatment programme at 8 weeks (measure of treatment response) through filling out self-report questionnaires and experimental motor task testing, and (iii) a third visit followed through a telephonic interview at 12-months (measure of relapse). Results: Motor timing alone predicted 27 percent of the variance in alcohol self-efficacy score change, and 25 percent variance in cocaine self-efficacy change scores at treatment completion. Specifically, spatial errors, synchronization errors and inter- response interval errors of a spatial tapping task at baseline predicted self-efficacy in alcohol self-efficacy. Cocaine self-efficacy was predicted by spatial errors and contact times of a spatial tapping task at very high tempi (300 ms) only. The high rate of dropout at 12 months post-treatment did not allow for further analysis of the prognostic value of motor timing on relapse. Conclusions: The results of this investigation show us that motor timing holds prognostic value with regard to treatment outcomes. Motor timing predictors for relapse require further investigation going forward.